Assessing the frequency and drivers of early‐greening in broad‐leaved woodlands along a latitudinal gradient in southern Africa. (6th October 2016) - Whitecross, Melissa A.; Witkowski, Ed T. F.; Archibald, Sally
Abstract: Savannas are the only deciduous system where new leaf flush pre‐empts the onset of suitable conditions for growth, a phenological phenomenon known as early‐greening. Limited understanding of the frequency and drivers of the occurrence of early‐greening in southern African savanna trees exists. We aimed to estimate the frequency of early‐greening events across southern Africa and investigated potential environmental drivers of green‐up. We selected and compared seven broad‐leaved woodland sites where Burkea africana was a dominant species using remotely sensed data along a latitudinal gradient from South Africa to Zambia. Normalized difference vegetation index (NDVI) values were extracted from the Moderate Resolution Imaging Spectroradiometer (MODIS) satellite imagery at each site from January 2002 to June 2014. Using an austral year (July 1st–June 30th), early‐greening was recorded if the green‐up start date occurred prior to the onset date of seasonal rainfall. A latitudinal gradient of early‐green‐up was detected across southern Africa ( R 2 = 0.74) with the two most northerly (Zambian) sites showing the earliest and most consistent green‐up start dates (3 October ± 5.34 days). A strong latitudinal gradient was observed between the variability in the amount of rainfall in the first 6 months of green‐up and the green‐up start dates across southern Africa ( R 2 = 0.92). Photoperiod appeared to play a role in areas where the onset of rainfall commenced late into the austral year. Mean maximum temperatures recorded 10 days prior to green‐up start dates suggested a potential threshold of about 35°C, which could drive early‐greening in the absence of rainfall. Correlations between the proportion of early‐greening years and the above mentioned environmental factors indicated that rainfall variability had the strongest influence over the observed phenological gradient ( R 2 = 0.96). Understanding early‐greening in complex savanna systems is a vital step in furthering predictive phenological models under changing climatic conditions.